Diagnostic value of fundus examination in familial adenomatous polyposis. Issue 9 (1st September 1997) - Tiret, Anne; Taiel-Sartral, Magali; Tiret, Emmanuel; Laroche, Laurent
Abstract : BACKGROUND: Multiple, bilateral lesions of congenital hypertrophy of the retinal pigment epithelium (CHRPE) have been described in patients suffering from familial adenomatous polyposis (FAP) since 1980. This study aimed to determine a reliable diagnostic criterion, based on the size and number of retinal CHRPE lesions, allowing the screening of patient carriers of the gene responsible for FAP. METHODS: 32 control subjects and 144 patients belonging to 85 FAP families were studied, divided into 124 carriers of the genetic alteration and 20 non-carriers. RESULTS: In carriers of the deleted gene, multiple, bilateral retinal lesions were consistently observed. Lesion situation, size, shape, and degree of pigmentation were variable however. A positive criterion for FAP was defined as the presence of at least four lesions whatever their size, or at least two lesions one of which is large. This criterion showed a high sensitivity (0.68) and a maximal specificity (1). Within each family, the retinal phenotypic expression was homogeneous. CHRPE lesions were observed in two thirds of the FAP families and absent from the remaining third. CONCLUSION: By using this new positive diagnostic criterion, fundus examination allows early detection of those children carrying the gene responsible for FAP in families positive at ocular examination.